RELATION OF INBREEDING OF HORSES OF THOROUGHBRED BREED WITH DEGREE OF HOMOZYGOSITY OF MICROSATELLITE LOCI OF DNA - Melnyk О.V. (Bìologìčnij Vìsnik Melìtopolʹsʹkogo Deržavnogo Pedagogìčnogo Universitetu Imenì Bogdana Hmelʹnicʹkogo, 2013)
The degree of homozygosity of some 39 Thoroughbred horses was estimated from microsatellite analysis data. The power of inbreeding was detected towards horse pedigree. We suggested the use of genetic analysis of microsatellite loci of DNA for the determination of actual level of inbreeding.